Clinical Utility of the Prenatal Ultrasound Score of the Placenta Combined with Magnetic Resonance Imaging in Diagnosis of Placenta Accreta during the Second and Third Trimester of Pregnancy. (15th June 2022) - Zhang, Jing; Dong, Pingping
Abstract : Objective . The aim is to explore the clinical utility of the prenatal ultrasound score of the placenta combined with magnetic resonance imaging (MRI) in diagnosis of placenta accreta during the second and third trimester of pregnancy. Materials and Methods . A total of 108 pregnant women with suspected placenta accreta treated in Wuhan Hankou Hospital and Yantaishan Hospital of Yantai from January 2019 to January 2022 were retrospectively analyzed, the enrolled pregnant women received MRI examination because of suspected results of ultrasonic diagnosis, and by taking pathologic findings as the gold standard, the diagnostic efficacy of the ultrasound score, MRI, and their combination to placenta accreta during the second and third trimester of pregnancy was analyzed, and the diagnostic sensitivity, specificity, the positive predictive value, and the negative predictive value of these diagnostic modalities were evaluated. Results . Among 108 patients with suspected placenta accreta, 75 with pathologically confirmed placenta accreta were included in the accreta group, and 33 without placenta accreta were included in the non-accreta group; no statistical between-group differences in the patients' age, gestational weeks, educational degree, and other general data were observed (P > 0.05 ), but the history of cesarean section, history of induced abortion, and incidence rate of placenta praevia were significantly higher in the accreta group than in the non-accreta group (P < 0.05 ); the ultrasound score was significantly higher in the accreta group than in the non-accreta group (P < 0.05 ); the incidence rates of signs of "placental heterogeneity" and "bulge of lower segment of the uterus and local thickening of the placenta" were obviously higher in the accreta group than in the non-accreta group (P < 0.05 ); according to the comparison with pathologic findings, the accuracy rate, sensitivity, specificity, the positive predictive value, and the negative predictive value of combined diagnosis were significantly higher than those of single application of the ultrasound score and MRI diagnosis (P < 0.05 ); and ROC analysis found that the area under the curve of combined diagnosis was obviously larger than that of the ultrasound score and MRI diagnosis (P < 0.05 ). Conclusion . A combining prenatal ultrasound score of the placenta with MRI plays an important role in the diagnosis of placenta accreta during the second and third trimester of pregnancy, which can further improve the diagnostic accuracy rate of placenta accreta and provide significant guidance in preventing high-risk complications during the perinatal period.